2008
DOI: 10.1007/s10815-008-9264-8
|View full text |Cite
|
Sign up to set email alerts
|

Abnormally low expression of connexin 37 and connexin 43 in subcutaneously transplanted cryopreserved mouse ovarian tissue

Abstract: Purpose To analyze the gap junction proteins connexin 37 (Cx37) and connexin 43 (Cx43) after subcutaneous transplantation of cryopreserved mouse ovarian tissue. Methods Expression of gap junction genes was assessed by immunohistochemistry and real-time polymerase chain reaction (PCR) in transplanted cryopreserved ovarian tissue compared with that of normal ovarian tissue. Apoptosis of ovarian cells was evaluated by using the terminal deoxynucleotidyl transferase-mediated biotinylated deoxyuridine triphosphates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 36 publications
(49 reference statements)
2
8
1
Order By: Relevance
“…The increase in Cx43 mRNA level after 4 days of DMBA exposure potentially indicates an anti-apoptotic role for ovarian CX43. Consistent with this posit, at the time point when follicle loss was observed (unpublished data), Cx43 mRNA and protein were decreased by DMBA exposure which is consistent with lower expression of Cx43 mRNA and protein expression in cryopreserved apoptotic mouse ovarian tissue (Lee et al , 2008). This decrease in Cx43 mRNA and protein is also associated with increased caspase 3 protein in ovaries treated with the same DMBA concentrations (Ganesan et al ., 2013).…”
Section: Discussionsupporting
confidence: 75%
“…The increase in Cx43 mRNA level after 4 days of DMBA exposure potentially indicates an anti-apoptotic role for ovarian CX43. Consistent with this posit, at the time point when follicle loss was observed (unpublished data), Cx43 mRNA and protein were decreased by DMBA exposure which is consistent with lower expression of Cx43 mRNA and protein expression in cryopreserved apoptotic mouse ovarian tissue (Lee et al , 2008). This decrease in Cx43 mRNA and protein is also associated with increased caspase 3 protein in ovaries treated with the same DMBA concentrations (Ganesan et al ., 2013).…”
Section: Discussionsupporting
confidence: 75%
“…The follicular loss during the cryopreservation and thawing processes is mediated by apoptotic mechanisms 112 and it has been estimated by measurements of follicular density with standard histology, 107 live/dead cell assays 109 or by assessment after culture of the cortical strips 113 or isolated follicles from the cortex 111 . There are no signs of DNA fragmentation in oocytes after cortical cryopreservation, 114 but granulosa cells seem to be altered both structurally and functionally 115,116 . A standard slow freezing protocol used for human cortex slices will cause injuries to the stroma cells, despite the high follicular survival 111 .…”
Section: Ovarian Transplantationmentioning
confidence: 99%
“…111 There are no signs of DNA fragmentation in oocytes after cortical cryopreservation, 114 but granulosa cells seem to be altered both structurally and functionally. 115,116 A standard slow freezing protocol used for human cortex slices will cause injuries to the stroma cells, despite the high follicular survival. 111 The use of rapid freezing protocols that transform the tissue fluid into a glass state (vitrification) may minimize injuries related to cryopreservation.…”
Section: Ovarian Cortex Cryopreservation and Transplantationmentioning
confidence: 99%
“…Previous studies suggested that the expression of most genes changed during ovarian vitrification [3,4]. Additionally, the expression of the reference gene GAPDH decreased in vitrified/warmed ovarian tissue compared with non-vitrified ovaries [5,6]. Whether expression of other reference genes changed during ovarian vitrification is unknown.…”
Section: Introductionmentioning
confidence: 99%